Making images move handmade cinema and other arts - Zinman, Gregory (Oakland, California University of California Press, 2020)
"Making Images Move reveals a new history of the moving image as told through its engagement with other media and art forms. Think of a Pollock or a Kandinsky that moves, a film created by scratching directly onto the celluloid, or a mechanical apparatus that fractures light and bends time. These moving-image artworks, and the tools and techniques that make them, open up new conversations about the production, meaning, and significance of the moving image. Indeed, the power of cinema has long been rooted in its photographic representation of the world and its ability to marshal images in the service of fictional or documentary narratives. But removing the camera from a study of film reshapes our understanding of cinema's past and its possibilities. From painted film to kinetic art, and from psychedelic light shows to video synthesis, Gregory Zinman recovers the range of forms, tools, and intentions that make up cinema's shadow history, enlightening our awareness of the intersection of art and media in the twentieth century, and deepening our understanding and appreciation of what is to come"--Provided by publisher
Introduction : A shadow history of the moving image -- Between canvas and celluloid : Visual music, motion paintings, and cameraless photography -- Abstractions in time : Painting and scratching on film -- By chemicals, by body, by mechanism : Other handmade methods -- Beyond the frame : Cameraless questions of politics and representation -- Light in motion : The moving image between the plastic arts and cinema -- Making space, making time : Light art of the 1950s and 1960s -- Forms of radiance : The practice and significance of the psychedelic light show -- Video art : Analog circuit palettes, cathode ray canvases -- Conclusion : Handmade moving images in the digital era
Print version record
Includes bibliographical references and index
JSTOR
Keywords: Motion pictures -- Production and direction -- History; Animated films -- Production and direction -- History; Computer animation -- Production and direction -- History; Video art -- Production and direction -- History; Cinéma -- Production et réalisation -- Histoire; ART -- Film & Video; Motion pictures -- Production and direction; History